Perceptions of Manspreading - Peden, Blaine F.; Xhunga, Nensi; Coulter, Lane (My University, 2018)
Manspreading refers to males on public transport who sit with legs spread apart to encroach on adjacent seats. The Oxford Dictionary added manspreading in 2015. Manspreading occurred so often in New York City that public service ads were put in subway cars telling men to refrain (Fitzsimmons, 2014).The purpose of our study was to examine people’s perceptions of this act via our survey in order to determine its relevance in social media and pop culture. Participants were given a survey assessing the relationship between four variables: compassion toward others and perceived inconvenience toward an image shown as a function of gender as well as circumstance of the image. We analyzed the results to determine a significant effect of gender and circumstance of image on perceived inconvenience of the situation.
Color poster with text, graphs, and images.
Keywords: Public transportation; Gender norms; Social psychology; Manspreading; Posters